Social Support and Job Insecurity in Outsourced Employees - Fachrudin, Rony; Prihastuty, Rahmawati (Journal of Social and Industrial Psychology, 2023)
Industry in Indonesia is increasing, so companies are required to continue to focus on production. To obtain efficiency and company profits using outsourced employees from labor supply companies. Outsourced employees work for a company through a company providing labor. With the existence of a fixed-time work system, outsourced employees have concerns about their future. Several factors influence the emergence of job insecurity, including social support. Therefore, this study aims to determine the relationship between social support and job insecurity among outsourced employees. This study uses a quantitative correlational design. The sampling technique used is saturated sampling, with a total sample of 83 outsourced employees. The instruments used were a social support scale comprising 26 items, a quantitative dimension of the job insecurity scale of 3 items, and a qualitative dimension of 4 items. The social support scale has a reliability value of 0.886, a quantitative dimension of the job insecurity scale of 0.604, and a qualitative dimension of job insecurity of 0.786. The analysis technique uses the Pearson correlation with the help of data processing software. The research results showed that the correlation value of social support with job insecurity in the quantitative dimension was r = 0.338 with p = 0.002 <0.05. Furthermore, the qualitative dimension's correlation value of social support with job insecurity was r = -0. 228 with p = 0.008 < 0.05. These results show that the hypothesis proposed by the author is declared accepted even though the direction of the relationship is different.